2019
DOI: 10.22146/jik.52140
|View full text |Cite
|
Sign up to set email alerts
|

Status Ergonomi Pekerja Sektor Kehutanan di Indonesia: Kelelahan Fisik-Mental-Sosial, Kepuasan Kerja, Konsep Sumber Bahaya, dan Konsep Biaya Kecelakaan

Abstract: Sustainable forest management requires attention to the protection of occupational safety and health (OSH), in addition to attention to aspects of work productivity, and the welfare of managers/ workers. In Indonesia, these four aspects, which are the main objectives of ergonomics studies, have not received much attention, although forest management activities are activities with a high risk of OSH disorders. This study aims to present an overview of the conditions of physical-mental-social fatigue, musculoske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 3 publications
1
11
0
2
Order By: Relevance
“…The finding that being permanent workers is associated with high job satisfaction also has been verified in another study carried out to permanent workers. This study confirmed that status as permanent workers related to a high level of job satisfaction (Yovi 2019). It seems that the level of dependency on forestry work to make a living, which is quite high in these two previous studies (80-100% of monthly income derived from forestry work), is the reason behind different employment status preferences.…”
Section: Job Satisfactionsupporting
confidence: 84%
See 3 more Smart Citations
“…The finding that being permanent workers is associated with high job satisfaction also has been verified in another study carried out to permanent workers. This study confirmed that status as permanent workers related to a high level of job satisfaction (Yovi 2019). It seems that the level of dependency on forestry work to make a living, which is quite high in these two previous studies (80-100% of monthly income derived from forestry work), is the reason behind different employment status preferences.…”
Section: Job Satisfactionsupporting
confidence: 84%
“…These groups of workers are field workers who use the physical while doing their work. It should be noted that different situations occurred in forest inventory workers who have a high anxiety disorder (Yovi 2019). The work location and work characteristics among inventory workers seem to be a determining factor for the occurrence of severe mental fatigue symptoms.…”
Section: Cumulative Fatigue Symptommentioning
confidence: 97%
See 2 more Smart Citations
“…Angka ini sangat mempengaruhi kondisi finansial pekerja di kedua kelompok. Sebagai perbandingan, ratarata rasio belanja makanan terhadap total penghasilan bulanan pada kelompok operator dan supervisor masing-masing adalah 53% (Yovi & Yamada, 2019) dan 46% (Yovi, 2019). Kedua angka ini jauh melebihi angka yang diperoleh dari pengamatan terhadap nilai belanja makanan pada keluarga dengan kemampuan ekonomi terbatas (lemah) (Castner & Mabli, 2010).…”
Section: Karakteristik Respondenunclassified